Improving the human–robot interface for telemanipulated robotic long bone fracture reduction: Joystick device vs. haptic manipulator. Issue 1 (25th September 2017) - Suero, Eduardo M.; Hartung, Tristan; Westphal, Ralf; Hawi, Nael; Liodakis, Emmanouil; Citak, Musa; Krettek, Christian; Stuebig, Timo
Abstract: Objectives: Intramedullary nailing is the treatment of choice for femoral shaft fractures. However, there are several problems associated with the technique, e.g. high radiation exposure and rotational malalignment. Experimental robotic assistance has been introduced to improve the quality of the reduction and to reduce the incidence of rotational malalignment. In the current study, we compare two devices for control of the fracture fragments during telemanipulated reduction. Methods: Ten male and ten female subjects were asked to participate as examiners in this experiment. A computer program was developed to render and manipulate CT‐based renderings of femur fracture bone fragments. The user could manipulate the fragments using either a simple joystick device or a haptic manipulator. Each examiner performed telemanipulated reduction of 10 virtual fracture models of varying difficulty with each device (five in a 'training phase' and five in a 'testing phase'). Mixed models were used to test whether using the haptic device improved alignment accuracy and improved reduction times compared to using a joystick. Results: Reduction accuracy was not significantly different between devices in either the training phase or the testing phase ( P  > 0.05). Reduction time was significantly higher for the Phantom device than for the Joystick in the training phase ( P  < 0.0001), but it was no different in the testing phase ( P  = 0.865). High spatial ability with electronics had a significant effect on the alignment of fracture reduction and time to reduction. Conclusions: The Joystick and the Phantom devices resulted in similarly accurate reductions, with the Joystick having an easier learning curve. The Phantom device offered no advantage over the Joystick for fracture telemanipulation. Considering the high cost of the Phantom device and the lack of a demonstrable advantage over the Joystick, its use is not justified for implementation in a fracture telemanipulation workflow. The Joystick remains as a low‐cost and effective device for developing 3D fracture telemanipulation techniques.